(untitled) (Bangladesh Journal of Agricultural Research, 2026)
Bottle gourd needs frequent watering with fertilization to get a potential yield. The experiment was conducted in the Irrigation and Water Management Division, Bangladesh Agricultural Research Institute (BARI), Gazipur, during the Rabi season (2017–2020) to determine fruit yield, water productivity, and net return. There were five irrigation treatments such as ring basin irrigation at 7 days interval (T1) with recommended fertilizer, drip-fertigation at an alternate day with 0, 20, 35, and 50% (T2-T5) less nitrogen (N) potassium (K) than the recommended doses. T4 gave the significantly highest fruit yield (39.30 t ha-1). Drip-fertigation system saved 50% of seasonal water than the ring basin method. Treatment T4 gave the highest water productivity (17 kg m-3) and benefit-cost ratio (BCR) (3.16). Therefore, it can be concluded that bottle gourd can be irrigated every alternate day through a drip-fertigation system using 35% less NK than the recommended doses to get a higher yield, water productivity, and net return. Bangladesh J. Agril. Res. 48(1): 79-89, March 2023